2005
DOI: 10.1088/0031-9155/50/21/n01
|View full text |Cite
|
Sign up to set email alerts
|

An innovative phantom for quantitative and qualitative investigation of advanced x-ray imaging technologies

Abstract: Development, characterization, and quality assurance of advanced x-ray imaging technologies require phantoms that are quantitative and well suited to such modalities. This note reports on the design, construction, and use of an innovative phantom developed for advanced imaging technologies (e.g., multi-detector CT and the numerous applications of flat-panel detectors in dual-energy imaging, tomosynthesis, and cone-beam CT) in diagnostic and image-guided procedures. The design addresses shortcomings of existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 6 publications
0
20
0
1
Order By: Relevance
“…Although the spatial structure of the cylindrical phantom is relatively simple, different contrast levels offered by different inserts provide an opportunity to evaluate reconstruction contrast and spatial resolution. The anthropomorphic head phantom was designed for realistically simulating human head [27], it features not only a natural human skeleton but also contrast-detail spheres approximating soft tissues. These fine and low-contrast structures pose challenges for tasks of image reconstruction from reduced numbers of projections and provide opportunities for evaluating algorithm performance.…”
Section: Cbct System and Data Acquisitionmentioning
confidence: 99%
“…Although the spatial structure of the cylindrical phantom is relatively simple, different contrast levels offered by different inserts provide an opportunity to evaluate reconstruction contrast and spatial resolution. The anthropomorphic head phantom was designed for realistically simulating human head [27], it features not only a natural human skeleton but also contrast-detail spheres approximating soft tissues. These fine and low-contrast structures pose challenges for tasks of image reconstruction from reduced numbers of projections and provide opportunities for evaluating algorithm performance.…”
Section: Cbct System and Data Acquisitionmentioning
confidence: 99%
“…FWHM was analyzed from a 2D gaussian fit to axial images of the wire, taking the average of the FWHM in the x and y directions as the reported value, unless otherwise specifically noted. CBCT image quality was assessed in reconstructions of an anthropomorphic head phantom 30 containing soft-tissue simulating contrast-detail spheres ͑11-103 HU; 1.6-12.7 mm diameter͒ and a natural human skeleton. Figures 1͑b͒-1͑e͒ illustrate CBCT image quality in coronal, sagittal, axial, and volume renderings from a full FOV 3D reconstruction of the head phantom using the geometric calibration method.…”
Section: Iib Image Quality Evaluationmentioning
confidence: 99%
“…3 The study reported here investigates the lowdose limits of lung nodule detectability in volume CT and identifies optimal low-dose reconstruction techniques particularly with regard to body habitus ranging from average to obese. A volume CT scanner and anthropomorphic phantom 7 form the basis of the study. The experimental variables include factors related to imaging dose ͑kVp and mAs͒ and image reconstruction ͑slice thickness and reconstruction filter͒, and low-dose detectability limits are identified by means of multiple-alternative forced-choice ͑MAFC͒ human observer tests.…”
Section: Introductionmentioning
confidence: 99%